Vlsi Architecture of Mimo Detector Using Fixed Complexity Sphere Decoding - Mathana, J.M; Rekha, P; Anitha, V Sai; Suchitra, B; Bavithra, K.B (Review of Information Engineering and Applications, 2014)
Fixed Sphere Decoding is a near optimum tree search detection technique for the spatial multiplexing scheme. The algorithm performs a fixed number of operations to detect the signal independent of the noise level and channel conditions. In this paper, a Soft Input Soft Output Fixed Complexity Sphere Decoding algorithm is proposed for the MIMO receiver using 16 QAM modulation scheme. As the system performance was far from the channel capacity limit, MIMO channel could not support higher spectral efficiencies. Therefore, to obtain power efficiency very close to the Shannon limit, Turbo codes are implemented in MIMO system and provide higher spectral efficiency. The proposed FSD detector is capable of providing a throughput of 1.18 Gbits/s with a critical path delay of 9.603 ns.